Pengaruh LATIHAN AGILITY LADDER DAN CONE DRILLS TERHADAP KETERAMPILAN TENDANGAN SABIT ATLET PUTRA PERSINAS ASAD SEMARANG (Indonesian Journal for Physical Education and Sport, 2020)
This study aims to determine the training of agility ladder and cone drills on sickle kick skills in male athletes persinas asad semarang. This study uses quantitative methods with test and measurement technique that are processed with t-test statistics using a short formula with a significance level of 5%. The population of this research is 24 male athletes of Persinas Asad Semarang. Because the numbers are small, all athletes are sampled (Total Sampling). The results of the study are as follow, from the preliminary test statistical calculations the two forms of training obtained the results of t count greater than t table namely 3,413 > 2,210 so it proved the effect of agility ladder and cone drills training on sickle kick skills in the male athlete Persinas Asad Semarang, then obtained data Mean Xa > Xb is 83.42 > 80.53. Therefore, agility ladder training has better potential than cone drills.